STUDENTS’ PERCEPTION OF COOPERATIVE LANGUAGE LEARNING-IN EFL LEARNERS’ CLASSROOM - Barri Nikko; Sarah Salsabila (NextGen Education Review Journal, 2023)
Student perception plays a crucial role in determining their understanding and engagement in the classroom. By understanding students' perceptions, teachers can effectively develop a revitalizing learning environment that caters to their specific needs. With this objective in mind, a research study was conducted to investigate the perceptions of twenty-eight students from SMKN 1 Kedawung regarding the implementation of cooperative learning. The findings revealed that students responded positively to cooperative learning, which proved to enhance their academic achievements, motivation, and social values. To gather data, a survey questionnaire was distributed among the participants to gauge their perceptions of the cooperative learning approach employed in class. Overall, the study demonstrates that cooperative learning is an effective method for classroom instruction, as it not only motivates students but also positively impacts their academic and social development.